The Relevance of the Philosophy of Positivism in the Development of Modern Science - Zainol Hasan; Hafizh Idri Purbajati; Al Munip; Firdaus; Irman Putra (Universitas Muhammadiyah Palu, 2024)
The philosophy of positivism, rooted in the thought of Auguste Comte, plays a crucial role in the development of modern science. This research explores the relevance of positivism in the contemporary context, focusing on the application of empirical methodologies and interdisciplinary collaboration. Through qualitative analysis, the research shows that positivism remains a valid foundation for scientific research, enabling researchers to produce reliable and applicable knowledge. The application of positivism in new technologies paves the way for innovation and increases the effectiveness of solutions to complex social problems. In addition, the social impact of this approach is seen in increased public awareness and evidence-based decision-making. The results of this study suggest the need for the integration of positivism with other methods to enrich the understanding and application of science in addressing future challenges. Thus, this study makes an important contribution to the understanding of the positive role of positivism philosophy in science and its impact on society.